A dsRNA‐degrading nuclease (dsRNase2) limits RNAi efficiency in the Asian corn borer (Ostrinia furnacalis). (19th November 2020) - Fan, Yun‐He; Song, Hui‐Fang; Abbas, Mureed; Wang, Yan‐Li; Li, Tao; Ma, En‐Bo; Cooper, Anastasia M.W.; Silver, Kristopher; Zhu, Kun Yan; Zhang, Jian‐Zhen
Abstract: The efficiency of RNA interference (RNAi) varies substantially among different insect species. Rapid degradation of double‐stranded RNA (dsRNA) by dsRNA‐degrading nucleases (dsRNases) has been implicated to cause low RNAi efficiency in several insect species. In this study, we identified four dsRNase genes ( OfdsRNase1, OfdsRNase2, OfdsRNase3 and OfdsRNase4 ) from the Asian corn borer ( Ostrinia furnacalis ) transcriptome database. Bioinformatic analyses showed that each deduced protein sequence contained endonuclease NS domains and signal peptides. Gene expression analysis revealed that OfdsRNase2 was exclusively expressed in the midgut of larvae. RNAi efficiency was investigated in 2‐d‐old fifth‐instar larvae (high expression of dsRNase2 ) and 2‐d‐old pupae (low expression of dsRNase2 ) by feeding or injecting dsRNA targeting a marker gene that encodes the lethal giant larvae protein ( OfLgl ). Our results showed that OfLgl only partially silenced the expression of OfLgl in pupae, but not in larvae, suggesting that OfdsRNase2 could contribute to lower RNAi efficiency in larval stages. This hypothesis was supported by our RNAi‐of‐RNAi experiment using a tissue culture technique where the silencing efficiency against the reporter gene, OfHex1, was significantly improved after knockdown of OfdsRNase2 . When double luciferase assays were performed to evaluate the role of the four dsRNases in vitro, only OfdsRNase2 expressed in S2 cells significantly affected RNAi efficiency by degrading dsRNA. Taken together, our results suggested that the degradation of dsRNA by OfdsRNase2 in the midgut contributed to low RNAi efficiency in O. furnacalis larvae. Abstract : Four dsRNA‐degrading nuclease (dsRNase) genes, including OfdsRNase1, OfdsRNase2, OfdsRNase3 and OfdsRNase4, were identified in Ostrinia furnacalis . The stage‐specific RNAi, RNAi of RNAi in tissue culture, and dual‐luciferase assays revealed that OfdsRNase2 contributes significantly to low RNAi efficiency in O. furnacalis .